Antidiarrhoeal and Antioxidant Effects of Centella asiatica Extract - GEORGE, MATHEW; JOSEPH, LINCY (Asian Journal of Chemistry, 2010)
The objective of the study was to find out the antidiarrhoeal and antioxidant effects of Centella asiatica extract in rats. For antioxidant studies spectrophotometric method was used, while for antidiarrhoel studies castor oil induced diarrhoeal method was used. The results obtained indicate that the extracts of Centella asiatica have antidiarrhoeal and antioxident activities. The extract at graded doses (100, 200, 400 and 600 mg/kg body weight) was investigated for antidiarrhoeal activity in term of reduction in the rate of defecation in castor oil-induced diarrhoea. To understand the mechanism of its antidiarrhoeal activity, the gastrointestinal transit and PGE2-induced intestinal fluid accumulation (enteropooling) were further evaluated. At graded doses (100, 200, 400 and 600 mg/kg body weight), the extract showed a remarkable antidiarrhoeal activity evidenced by the reduction in the rate of defecation up to 78.68 % of control diarrhoeal animals at the dose of 600 mg/kg body weight. The results are comparable to that of a standard drug loperamide (3 mg/kg body weight). The extract produced profound decrease in intestinal transit (8.26-55.67 %) at selected doses comparable to that of single intraperitoneal injection of standard drug atropine sulphate at doses of 0.1 mg/kg body weight. It significantly inhibited PGE2-induced enteropooling (22.10-57.12 %). The results indicated that the ethanol extract of the C. asiatica possessed significant antidiarrhoeal effect and substantiated the use of this herbal remedy as a non-specific treatment for diarrhoea in folk medicine. Centella asiatica also possessed antioxidant activity that can be attributed to the presence of glycosides and triterpenes. The obtained result compared with that of standard antioxidant curcumin.